Ayurvedic Management of Primary Dysmenorrhea with Sapthasara Arka (International Journal of Ayurveda and Pharma Research, 2024)
Dysmenorrhea is one of the most common gynecological conditions that affect the quality of life of women. The incidence of primary dysmenorrhea of sufficient magnitude to cause pain with incapacitation is about 15–25%. Udavartha, one among the Vathika Yonirogas, characterized by painful menstruation and relief of symptoms after blood discharge; can be symptomatically correlated to primary dysmenorrhoea. Sapthasara Kashaya, mentioned in Chikitsa Manjari, is indicated in the Ruja of Yoni, Hrith, Kukshi, and Prushta. The drugs in the Sapthasara Kashaya are Vathakapha samana and Vatanulomana in action. Methodology: Here is a case report of an 18-year-old girl who presented with complaints of severe pain during menstruation, low back ache, nausea, vomiting, and giddiness for the past 2 years. Her USG reports were found to be normal and so were diagnosed as a case of primary dysmenorrhoea. The patient was given 24ml of Sapthasara Arka with the same amount of water orally twice daily, half an hour before food, for 60 days. The assessment was done on 0th, 30th, 60th, and 90th days using the Visual Analogue Scale and the Verbal Descriptive Scale. Result: Signs and symptoms were significantly reduced on the 30th day of treatment and they were absent on 60th day and 90th day of follow-up. Conclusion: In primary dysmenorrhoea, the administration of Sapthasara Arka was found to be effective.